Kesehatan Lingkungan dan Pola Hidup Masyarakat - Arman Manalu (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Manalu A. 2019. Environmental health and community life patterns. In: Herlinda S et al. (Eds); Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 292-304. Palembang. Unsri Press. Environmental health is an ecological balance that must exist between humans and the environment in order to guarantee the health of humans (WHO). Environmental health is very important to support the lives of healthy people. The environment consists of two main elements, namely biotic and abiotic. Biotic elements are all living things such as humans, plants, animals, flora and fauna. Abiotic elements are water, air, soil, sun, wind. This research was conducted aiming to determine the effect of people's behavior and culture on the quality of environmental health carried out by qualitative descriptive methods. The condition of environmental health is not inseparable from the lifestyle, habits, culture of society, education and knowledge of environmental health. Behavior is a factor that plays a role of almost 60% in health determinants, in addition to environmental factors and is very closely related to the cultural factors of society. The habit of people disposing of hazardous waste to waterways and industry players around the watershed who dump various hazardous industrial wastes directly into the river without going through the waste treatment process causes damage to river ecosystems, and damage to rice plants due to getting contaminated water supplies of various pollutants and skin diseases. The community burns garbage mixed with hazardous materials, bushes, and burning forests to speed up the clearing of plantation land resulting in air pollution. For this reason, it is necessary to educate the community with various methods about the importance of environmental health for healthy and quality human life.Keywords: education, community culture, pollution